Development of a Frequency Modulated Continuous Wave radar for slow moving target detection - Nor Fatin binti Muhd Ariffin (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Frequency Modulated Continuous Wave (FMCW) radar system is frequently used for remote sensing applications which require high sensitivity and continuous monitoring. There are many factors that affected the radar's performance; they are including applied techniques, characteristic of detecting a target and experimental environment. Those factors also provide the impact on the expenses of the radar fabrication. This research aims to develop an inexpensive S-band FMCW radar with radar sensitivity improvement for slow moving target applications. The pre-design phase of the radar is simulated in Advanced Design System (ADS) 2014 software to find the radar's breakthrough. The proposed radar operates at 2.4GHz carrier frequency with 10.41dBm transmit power. It established a 2.8m range resolution from 53.2MHz bandwidth. A computer-based system is used for Data Acquisition (DAQ) system and digitalized signal process. Chirp period-bandwidth product of Frequency Modulated (FM) waveform and deramping process with maximum range of 200meters and Radar Cross Section (RCS), σ of 1m2 improve the radars' Signal to Noise Ratio (SNR) by 42dB. Next, the radar is tested in several experiments to evaluate the capability of the radar to determine range and velocity of the slow moving target. The experiments are conducted in a Microwave Laboratory of International Islamic University Malaysia. Fast Fourier Transform (FFT) method is used for analog to digital conversion. Additionally, Moving Target Indicator (MTI) - chirp cancellor technique is implemented on ranging measurement for clutter rejection. Based on the conducted experiments, the radar proves that it is able to detect the target that moves at very slow speed. It provides accurate measurement for a target which moves more than 1m/s speed with a 6.73% percentage error. It also achieves an accurate and precise range measurement for slow moving target detection with 0.18% percentage error. Hence, the proposed FMCW radar design is capable to provide high sensitivity performances despite its low-cost fabrication.